Estudio de factibilidad para la implementación de una empresa de consultoría para estudios de mercados ubicada en el cantón Quevedo, provincia de Los Ríos. año 2013 - Veintimilla Vera, Jaime Javier (2013)
The present study has as purpose to determine the feasibility of creation of a consultancy company for studies of markets and this located in the Cantón Quevedo Provincia of Los Ríos, Year 2013. For such a reason the investigative work begins with the following generalities of the company Justification, Problematización, Objectives, Hypothesis Contextual Marco of the Investigation, Studies of Market, Technician, Economic and Financial, conclusions and Recommendations, Bibliography and Annexes. For the present project we use the investigation of sources, since I endow us of the statistical, bibliographical data, internet, library, etc., in this investigation uses information provided by the Chamber of Commerce to carry out the offer projections and it demands. One works since with field investigation you elaborates a survey the same one that you applies to the companies that demand the service. The data that were obtained were subjected to classification, registration, tabulation. The consultant will offer advice in studies of markets guided to obtain excellent results, generating a circle of development virtue and employment, through the consultant's creation. The investigation was quantitative since it determined in form white and she/he specifies the level of technical feasibility and financial economic profitability that it would grant implementing a company dedicated to the consultancy of studies of markets. Regarding the feasible project, you uses logical that were employees to decipher what you/they reveal the data.